CANDIDIASIS: A COMPREHENSIVE REVIEW - Yodgorova N.T., Ravshanova M.S., (Central Asian Journal of Medicine, 2025)
Candidiasis is an opportunistic infection due to Candida, which can affect the oral cavity, vagina, penis, or other parts of the body. Identify the etiology of candidiasis medical conditions and emergencies. Untreated Candida infection carries the risk of leading to a systemic infection in which other organs can become involved and may lead to sepsis. This activity covers the presentation, examination, diagnosis, treatment, and management of this condition to enable healthcare practitioners to achieve optimal patient outcomes.